ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN SUBJEKTIF GANGGUAN PERNAPASAN PADA PETANI - I Kadek Dwi Arta Saputra,; A.A Istri Diah Indrasuari,; Ni Made Ayu Wulandari,; Ni Putu Ardiyanti,; Cokorde Gde Putra Pemayun, (Journal of Innovation Research and Knowledge, 2025)
Introduction: Farmers who spray pesticides without using Personal Protective Equipment (PPE), such as masks or respirators, are highly susceptible to respiratory disorders. Direct exposure to pesticide vapors or particles inhaled during work can lead to symptoms such as coughing, shortness of breath, and respiratory tract irritation, and may cause chronic lung diseases over time. Methods: This study used a quantitative research design with an analytic cross-sectional approach. The sampling technique applied was total sampling, involving all 33 farmers who met the inclusion criteria. Primary data were collected and analyzed using univariate and bivariate analysis. The Chi-square test was employed to determine the relationships between variables. Results: The study found that subjective complaints of respiratory problems were significantly more common among farmers aged ≥40 years (p = 0.006), with a work duration of ≥10 years (p = 0.028), and daily work hours of ≥8 hours (p = 0.0043). Additionally, smoking status (p = 0.031), poor use of PPE (p = 0.008), and high levels of pesticide exposure (p = 0.014) were also significantly associated with respiratory complaints.Conclusion: Farmer characteristics, including age, length of employment, working hours, smoking habits, PPE usage, and pesticide exposure levels, are associated with subjective respiratory complaints among farmers